Functional nano molecularly imprinted polymer for the detection of Penicillin G in pharmaceutical samples - Rahim, Zulaiha Abdul; Yusof, Nor Azah; Ismail, Suhainie; Mohammad, Faruq; Abdullah, Jaafar; Rahman, Norizah Abdul; Abubakar, Lawal; Soleiman, Ahmed A. (Springer, 2023)
In the present study, we demonstrated the synthesis of nanosized molecularly imprinted polymer (nanoMIP) particles via a miniemulsion polymerization strategy for the selective recognition of Penicillin G element, a β-lactam antibiotic (PenG-nanoMIP). The PenG-nanoMIP probe was developed by the mixture of functional monomer, methacrylic acid (MAA) and crosslinking agent, ethylene glycol dimethacrylate (EGDMA). The pre-polymerization of monomer-template mixture was emulsified into miniemulsion via sonication where the PenG-nanoMIP particles were obtained with an average diameter of 60–70 nm. Also, various MIPs were formed by taking different combinations of monomer to crosslinker and among all, the MIP formed with a ratio of 6:24 was chosen as the optimum formulation. In addition, the PenG-nanoMIP probe has been characterized thoroughly for the surface functionality (FTIR), morphological changes (FESEM-EDX), and particles diameter. Finally, the batch rebinding tests via UV–Vis were conducted to investigate that the PenG-nanoMIP 2 has the greatest binding capacity with 4.37 mg/g as compared to PenG-nanoMIP 1 and PenG-nanoMIP 3 having the binding capacities of 3.33 mg/g and 3.62 mg/g respectively. Based on the analysis, it can be suggested that PenG-nanoMIP 2 has offered the highest binding and selectivity for PenG.